A modernist Amazonian: Residential works of the architect Severiano Porto in Manaus/AM - Guerreiro , Ana do Nascimento; Abrahim , Ana Lúcia da Silva; Farias, Taise Costa de (Seven Editora, 2023)
The present research is the result of an extension project linked to the undergraduate course in architecture and urbanism of the University Nilton Lins and has as its main objective the analysis of four residential works of the architect Severiano Porto in the city of Manaus/AM. The concept analysis is characterized by a reflective and critical reading of the architecture, being essential for the knowledge of the processes and strategies of the architect’s residential projects. Sandoval Porto was one of the pioneer Brazilian architects to act in the Amazon region, where he sought a regional identity for modern architecture, being aware that the regional factors should be studied for proper application in the project. In this research, the residences will be analyzed: "Casa do Cafundó", "Casa Porto", "Casa Robert Schuster", and the "Casa Alexandre ale dos Santos"; Through a methodological roadmap that uses the redesign and 3d modeling for the understanding of the projects in the framework concept, constructive, functional and plastic. The research is based both on the relevant concept and conceptual of the works of the architect, as for the fact that these productions are still little known and documented. Thus, the present research aims also to contribute to a better understanding of the works of the architect Severiano Porto and the studies sore the architecture Amazonense. DOI:https://doi.org/10.56238/devopinterscie-263